Evaluation of Frozen Section Results in Patients Who Have Suspected Testicular Masses: A Preliminary Report - Tuygun, Can; Ozturk, Ufuk; Goktug, Hasan Nedim Goksel; Zengin, Kursad; Sener, Nevzat Can; Bakirtas, Hasan (Urology Journal, 2014)
Purpose: To report our experience with patients who have suspected testicular masses (STM) managed by ex vivo technique of testicular sparing surgery (TSS) after radical orchiectomy. Materials and Methods: Between 2007-2011 years, 10 patients with STM were evaluated by history, physical examination, testicular ultrasound and serum tumor markers. STM were defined as; no paratesticular lesions, size of the lesion smaller than 20 mm, and no known presence of elevated tumor markers or metastatic disease. The principles of TSS followed by radical orchiectomy were applied to the removed surgical specimen. Excised mass, multiple biopsies of the adjacent parenchyma and the remaining testis were sent for frozen-section analysis (FSA). Histopathologic sections were re-reviewed for definitive pathologic diagnosis. Results: The mean patient age, mean size and mean length of history of STM were 37 years (25-64), 17.5 mm (10-20) and 6 months (2-12). All STM were palpable and painless. Tumor markers were negative in all patients. Six tumors were benign (2 adenomatoid tumor, 1 epididymitis nodosa, 1 leydig cell tumor, 1 sertoli cell tumor, 1 fibrous pseudotumor) and 4 tumors were malignant (3 seminoma, 1 embryonal carcinoma) on definitive pathologic diagnosis. Excluding one benign lesion, FSA correctly determined 9 lesions and all malignant lesions. Three patients had testicular intraepithelial neoplasia (ones seminoma, ones embryonal carcinoma, ones adenomatoid tumor). Conclusion: Our preliminary report reveals that STM tend to be benign rather than malignant in nature. Also, a careful patient selection and an accurate FSA are crucial points for TSS and it has the potential to become the primary option in selected patients who have testicular lesions instead of the traditional method.